From performative to professional accountability: re-imagining 'the field of judgment' through teacher professional development. Issue 3 (4th May 2023) - Gore, Jennifer; Rickards, Bernadette; Fray, Leanne
ABSTRACT: The rise of performative culture in education and intensifying forms of test-based accountability have subjected teachers to a ubiquitous 'field of judgment' through which they are held to account. Within this context, professional development is consistently deployed as a key solution to stagnant or declining student outcomes. In this paper, we examine how accountability might be reimagined through one approach to professional development known as Quality Teaching Rounds (QTR). We draw on Foucault's notion of panopticism and Ball's influential writings on performativity to analyse interviews with 21 educators from 14 schools in New South Wales, Australia, conducted during a 2014–2015 randomised controlled trial. Participants highlighted the pervasiveness of testing and test results in shaping their experience of teaching in a system of perpetual surveillance where numbers bite deep into practice. By contrast, participation in QTR afforded teachers rare spaces of freedom within the structure of performativity to collaboratively focus on pedagogy. We argue meaningful professional development can alter the field of judgment and enable teachers to reclaim accountability on their own terms, while maintaining a clear focus on student outcomes.